Analisis Yuridis Tindak Pidana Pembunuhan Berencana: Studi Kasus Berdasarkan Berita Acara Pemeriksaan dari Laporan Polisi NO. POL LP/15/X/2016/POLDA NTT/RES ST/SEK LEWA/Sub Sektor Nggoa - Samara, Finsensius; Wardani, M Dhini Putri; Klau, Fransiskus Xaverius Seran; Bela, Anggrony Rambu Rauna; Widodo, Danendra Ricardo Ivander; Kitu, Maria Anjelica Deswita; Soi, Marselina Rahmita (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study analyzes a case of premeditated murder that occurred in Makaminggit Village, East Sumba Regency, East Nusa Tenggara, based on report no. lp/15/x/2016/polda NTT, dated July 20, 2012. This case involves a man named YULIUS MUTU ROMU alias LIUS as the suspect, FREDERIKA KAITA ATA ENDI alias EDA as the reporter, KATUHI LALANG alias BAPAK EDA and KONDA NGGUNA alias ATU KONDA as the victims. The case was accompanied by a legal representative appointed by the police named UMBU TONGA, SH. This study uses a normative legal research method with a case approach and descriptive analysis of the examination records (BAP) as the primary data source. Our research findings on this case indicate that: (1) this case is eligible to proceed to trial based on the official report, the defendant's statement which is transparent and honest, along with the evidence; (2) all elements of Article 340 of the Criminal Code have been fulfilled.